Factors Affecting Mammalian Embryo Culture: A Detailed Review - Sahil Sanghvi; Anagha Rane; Shivangi Sanghvi; Kewal Mishra; Christine O Brien; Cindy M.P. Duke (International Journal of Cell Biology and Cellular Functions, 2026)
Human IVF has made remarkable progress, but optimizing the in vitro environment remains essential and crucial for supporting embryo development and improving overall clinical outcomes in assisted reproductive technologies (ART). Even with advances in complex culture media, incubator design, and laboratory workflows, embryos grown outside the body are still exposed to chemical and physical stressors that can significantly affect their developmental potential. In this review, we discuss key chemical stressors, including oxidative stress caused by elevated oxygen levels, ammonium accumulation from amino acid breakdown, pH instability, volatile organic compounds (VOCs), and variability in albumin sources. Physical stressors such as temperature fluctuations, light exposure, mechanical vibration, electrostatic discharge, and electromagnetic fields also influence embryo metabolism, genomic stability, mitochondrial function, and epigenetic programming. Emerging technologies, including low-oxygen incubators, recombinant human albumin, real-time environmental sensors, microfluidic culture systems, advanced optical platforms, and vibration isolated workstations, show promise in reducing these risks. Evidence suggests that interactions between multiple stressors may amplify embryotoxic effects, impacting embryo growth and development. Overall, maintaining physiological culture conditions and minimizing laboratory-induced stress are crucial for supporting embryo development, viability and ensuring the safety and success of ART.
Keywords: Embryo; Embryo Culture; Gametes; IVF; Oocyte; Sperm